Educational Innovation as a Factor of Modernization of Teaching System - Xaydarova Oliya (Genius Journals, 2022)
The article describes innovative approaches, modernization of the education system, principles of education, technology of the educational process, design of the educational process.
Keywords: Innovative approach; innovative teaching technologies; modernization; modernization of the teaching process